2015
DOI: 10.1142/s0219455415400295
|View full text |Cite
|
Sign up to set email alerts
|

Composite Action Between Cold-Formed Steel Beams and Wood-Based Floorboards

Abstract: An experimental investigation has been conducted into the degree of shear interaction between cold-formed steel floor joists and wood-based flooring panels and the resulting benefits derived in terms of composite action. A series of four-point bending tests have been carried out to evaluate the overall system behavior, while material tests have been performed to accurately define the material properties of each component of the examined system. Two different shear transfer mechanisms were examined: self-drilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 9 publications
1
27
0
1
Order By: Relevance
“…Observing a similar trend in the carbon steel data assembled herein, εu was also considered to depend on the ratio of yield stress fy to ultimate tensile stress fu. The experimental ultimate strains εu are plotted against the corresponding fy/fu ratios for the data from 537 hot-rolled and 272 cold-formed [41,43,45,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] carbon steel tensile coupon tests, as shown in Fig. 5.…”
Section: Predictive Expressions For εU and εShmentioning
confidence: 99%
“…Observing a similar trend in the carbon steel data assembled herein, εu was also considered to depend on the ratio of yield stress fy to ultimate tensile stress fu. The experimental ultimate strains εu are plotted against the corresponding fy/fu ratios for the data from 537 hot-rolled and 272 cold-formed [41,43,45,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] carbon steel tensile coupon tests, as shown in Fig. 5.…”
Section: Predictive Expressions For εU and εShmentioning
confidence: 99%
“…The key measured material properties of the 3 mm thick cold-formed steel are listed in Table 2, together with those of the previously tested 1.5 mm material (Kyvelou et al 2015). It may be observed that the proof strength σ 0.2 of the corner coupons is, on average, 17% higher than that of the flat coupons.…”
Section: Tensile Steel Coupon Testsmentioning
confidence: 97%
“…A detailed explanation of the tensile coupon testing procedure, which was conducted according to BS EN ISO 6892-1 (CEN 2009), is presented by Kyvelou et al (2015). The measured material stress-strain curves, up to 2% strain, are illustrated in Fig.…”
Section: Tensile Steel Coupon Testsmentioning
confidence: 99%
See 2 more Smart Citations